2015
DOI: 10.1039/c5cp00428d
|View full text |Cite
|
Sign up to set email alerts
|

A molecular dynamics study of CaCO3 nanoparticles in a hydrophobic solvent with a stearate co-surfactant

Abstract: Stearates containing overbased detergent nanoparticles (NPs) are used as acid neutralising additives in automotive and marine engine oils. Molecular dynamics (MD) simulations of the self-assembly of calcium carbonate, calcium stearate as a co-surfactant and stabilising surfactants of such NPs in a model explicit molecular hydrophobic solvent have been carried out using a methodology described first by Bodnarchuk et al. [J. Phys. Chem. C, 2014, 118, 21092]. The cores and particles as a whole become more elongat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The function of many lubricant additives depends on chemical reactions, which are generally not considered in classical MD simulations. Despite this, classical MD simulations have given unique insights into the behaviour of a range of lubricant additives including detergents [207,208], dispersants [209,210], viscosity modifiers [91,92,211], anti-wear additives [212][213][214][215], and corrosion inhibitors [216][217][218]. The most widely studied class of lubricant additives with MD are friction modifiers [219], which are a wellsuited application of confined NEMD simulations.…”
Section: Nemd Simulations Of Lubricant Additivesmentioning
confidence: 99%
“…The function of many lubricant additives depends on chemical reactions, which are generally not considered in classical MD simulations. Despite this, classical MD simulations have given unique insights into the behaviour of a range of lubricant additives including detergents [207,208], dispersants [209,210], viscosity modifiers [91,92,211], anti-wear additives [212][213][214][215], and corrosion inhibitors [216][217][218]. The most widely studied class of lubricant additives with MD are friction modifiers [219], which are a wellsuited application of confined NEMD simulations.…”
Section: Nemd Simulations Of Lubricant Additivesmentioning
confidence: 99%
“…In the third stage, steered MD and umbrella sampling was used to calculate the free energy of association between two nanoparticles of the same surfactant type, using the same number of species in the OB particle and water as in simulations D to F. The number of each species in the simulations is given in Table . The model nanoparticles in the simulations were performed using the Coulombic annealing and re-forming procedure invented and described in refs .…”
Section: Virtual Experiments Methodologymentioning
confidence: 99%
“…Resolution of this issue reduces to identifying the role that the water interface plays in determining the OB particle shape and also on the effective interaction energy as a function of separation between two OB particles. Our more recent molecular simulation studies have shown that even trace amounts of water interact strongly with the OB calcium carbonate core in the bulk oil. , Therefore, it might reasonably be expected that the effects of surrounding water in the LT experiment arrangement could be significant, although this issue has yet to be fully resolved. This is one of the objectives of this study.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations